2019
DOI: 10.1109/access.2019.2910737
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Phase-Coded Visual Stimuli for SSVEP-Based BCI

Abstract: This paper presents a method of binocular visual stimulation for brain-computer interfaces (BCIs) based on steady-state visual evoked potentials (SSVEPs) using phase-coded symbols. The proposed method's emphasis is on a binocular phase-coded visual stimulus, which is based on the phase differences between the left-and right-eye stimuli, and a symbol detection and recognition procedure based on SSVEP response of the left and right occipital lobes of the user's scalp, where the SSVEP response is obtained as elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Previous studies of EEG signals described that decreased beta (13-30 Hz) band power has been linked to visual attention (mental focus state) [24][25][26]. The SSVEP-BCI study investigated that the occipital lobe of the brain shows a significant role in SSVEP-BCI technologies [27]. Early studies of the working memory task found that the EEG power of the beta (13-30 Hz) band increased in the parietal and occipital lobes [23,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of EEG signals described that decreased beta (13-30 Hz) band power has been linked to visual attention (mental focus state) [24][25][26]. The SSVEP-BCI study investigated that the occipital lobe of the brain shows a significant role in SSVEP-BCI technologies [27]. Early studies of the working memory task found that the EEG power of the beta (13-30 Hz) band increased in the parietal and occipital lobes [23,28].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we used high temporal resolution electroencephalography (EEG) method to investigate the mental focus and lost-in-thought states of the BCI users. The first time our study explored the EEG neural marker including delta (1-4 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12), and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) bands in mental focus and lost-in-thought states at frontal and occipital lobes of the brain than in previous studies of SSVEP and EEG [6,[37][38][39]. According to our hypothesis, the power spectrum of EEG signals in mental focus state will increase more than in lost-in-thought state at the frontal lobe, because the frontal lobe is related to attention and working memory.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent advances in SSVEP-based BCIs have developed techniques and algorithms to overcome these obstacles. Several studies have proposed different stimulus design techniques to realize large number of targets with only few frequencies, but they have also suffered limitations [21,38,43,50,57,58,90]. Furthermore, a few researchers combined SSVEPs with P300 to generate more targets with less frequencies, but this was at the cost of task complexity, which eventually affected the performance of the system.…”
Section: Discussionmentioning
confidence: 99%
“…The phase defines the point of one cycle at which a wave is or starts. In SSVEP BCI, a phase shift can be used as a distinction between targets, i.e., as a coding method [46,70].…”
Section: Wave Parametersmentioning
confidence: 99%